BASIC ENGLISH TRAINING FOR STUDENTS TO IMPROVE STUDENTS’ ACADEMIC MOBILITY: COMMUNITY SERVICES AT AL-HUDA HIGH SCHOOL IN SOUTH LAMPUNG - Dwi Budi Setiawan; Dhiona Ayu Nani; Shiwi Angelica Cindiyasari (COMMENT: Journal of Community Empowerment, 2022)
Skills create favorable conditions for the development of activities and talents to achieve affordable and decent education. One of the additional skills that can be developed is the ability to speak English. Besides being an additional skill, English is also part of the education curriculum of high school students. This community service provides basic English training for students especially for Al-Huda High School students to improve their skill in English. We developed students’ skills by teaching steps to learn English in four ways: vocabulary, tenses/grammar, fluenting, and naturalizing. Mastering vocabulary is the main thing to learn English. Students are very enthusiastic in participating in this basic English training. This training really helps students to understand the basics of English, which is packaged in an attractive form, so students are very easy to understand. In addition, in this training students are not only invited to understand in theory, but also in practice such as singing songs in English.Keywords: Skills, English, Education, Community Service.